Pemikiran Ekonomi Ilmuwan Muslim Mazhab Alternatif Kritis - Farkhan Huzein; Rafid Naufal Aqil; Miko Ibnu Ibrahim; Muhammad Taufik Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In order to provide equal justice in all areas, Islamic economics focuses on the development of supply and demand principles, procedures, market controls, fair pricing, maximized wealth distribution, and of course, the prohibition of riba, gharar, and maisir. Finding the definition of the crucial alternative school is the purpose of this research. The research utilized literature research techniques derived from Islamic scholars' books and journals on economic theories. The findings of this study show that this institution encourages Muslims to criticize Islamic economics in addition to capitalism and socialism. As a result, claims made in Islamic economics must be verified by science. Timur Kuran criticized Islamic economic approaches that focus on justice. He felt that zakat would not be able to adequately distribute income because small-scale projects in mining, agriculture and raw material processing could be targeted, as was the case in the early days of Islam. He took issue with the fact that, while there was widespread agreement that commodity speculation was highly unjust, it was unclear whether it was still allowed.